Breaking self-misconceptions driven emotional loops of mba students to help them become responsible leaders - Sundararajan, Malavika; Sundararajan, Binod (Journal of Management and Business Education, 2023)
Responsible leadership training requires development of individuals who are both knowledgeable and emotionally mature so that they can overcome personal biases to make honest and ethical decisions that have a positive social impact within and outside the organization. Current MBA class exercises use a few trait-based surveys and basic techniques to manage one’s emotions along with leadership definitions that can be misinterpreted by students to be devoid of liable behaviors. Consequently, the problem of self-misconception persists with no change in students’ reasoning about the core problem that is causing their emotionally charged decision. Hence, most students fail to sustain their emotional management processes. To address this need to recognize and correct one’s self-misconceptions to uphold emotional maturity, our specific course of action is to address it holistically based on a preexisting Upanishadic model. The primary contribution of this paper is to bring to the forefront a practical, and useable model that can provide clear steps to refine one’s habitual orientations caused by self-misconceptions. We present the causal mechanism underlying the cognitive-emotional mechanisms wherein the core constructs are Knowing, Active and Inert qualities along six behavior influencing areas which elicit three distinct groups of emotions resulting in consequent decisions. Using a short case scenario-based exercise, we put forth steps students can take to develop responsible leadership qualities. Implications in the form of less stressful and happier workplaces are briefly discussed. A new definition of leadership is presented that helps one distinguish true leadership from notorious ones. The model and the accompanying steps help MBA students develop into fair, thoughtful, knowledgeable, compassionate, and truthful leaders, who work for the benefit of the entire society.